Analysis of financial sustainability to guarantee full access to cancer drugs (Research, Society and Development, 2021)
The high incidence of cancer cases has made it an evident public health problem worldwide. Public network managers in Brazil claim that the funds transferred are not sufficient to cover the costs of chemotherapy. This work provided an overview of the service offered by the SUS in the oncology care network in Pernambuco and evaluated the financial sustainability to ensure access to chemotherapy drugs in a reference hospital. This was an observational, analytical and retrospective study, carried out from 2015 to 2020. The cost of chemotherapy for breast cancer was evaluated and the incorporation of new treatments by CONITEC during the same period was analyzed. A total of 343,585 chemotherapy procedures were performed in the establishments evaluated and it was observed that breast cancer was the most costly neoplasm. It was also observed that the financing of cancer treatments remained stable, despite the inflationary and epidemiological evolution, with a loss in the incorporation of technologies. It was found that the costs of chemotherapy for breast cancer compromised 31.23% of the amount paid by the MS, and currently, with the readjustments in the period, this started to compromise 100.75%. When projecting the readjustments for the coming years, it was found that the budget would be committed at 121.6%, taking into account the same inflationary scenario. It was concluded that the current form of financing chemotherapy treatment for breast cancer did not prove to be financially sustainable in the evaluated scenario and that if new investments are not made, SUS patients will not benefit from new treatment technologies.